PEMBINAAN GURU DALAM PELAKSANAAN KURIKULUM MERDEKA BELAJAR MELALUI SUPERVISI KLINIS DI SMKN 8 PEKANBARU - MARSEFEL MARSEFEL (JURNAL ILMIAH MAKSITEK, 2022)
The problem in this study is that the Independent Curriculum is present to perfect the implementation of the 2013 Curriculum. The teacher's understanding of the implementation of the Independent Curriculum is still in the sufficient category, and needs development. teachers who do not fully understand the independent curriculum, the independent curriculum learning plans are not maximized and the evaluation of independent curriculum learning is not satisfactory. The type of research used in this study was the school action research method (PTS). The research location was carried out at SMKN 8 Pekanbaru. The research was carried out in the June-December semester of the 2022/2023 school year. The principal action research subjects were teachers at SMKN 8 Pekanbaru. The technique of collecting data from this school action research is through quantitative data obtained from observation and interviews. The data analysis technique used in this study is quantitative data analysis originating from observational data acquisition. The results of the study show that with guidance through clinical supervision teachers can understand more about the independent curriculum and apply it more easily in the learning system. 1) Learning the independent curriculum in the form of learning tools in accordance with the guidelines for making independent curriculum learning tools, namely analyzing learning outcomes (CP). 2) Implement an independent curriculum that begins with the implementation of a diagnostic assessment, carry out learning according to project-based teaching modules, both short-term projects and long-term projects, 3) carry out assessments or evaluations of learning to implement the independent curriculum including carrying out diagnostic assessments, implementing and processing formative and summative assessments and reporting learning outcomes .